Analysis of early pleural fluid samples in patients with mesothelioma: A case series exploration of morphology, BAP1, and CDKN2A status with implications for the concept of mesothelioma in situ in cytology. Issue 5 (10th February 2022) - Louw, Amber; van Vliet, Chris; Peverall, Joanne; Colkers, Shane; Acott, Nathan; Creaney, Jenette; Lee, Y. C. Gary; Chai, Siaw Ming
Abstract : BACKGROUND: The concept of mesothelioma in situ has been revisited and is a new World Health Organization diagnostic entity. The definition centers on ancillary techniques used in pleural mesothelioma (PM) assessment. At the authors' institution, most PM diagnoses are made on cytologic specimens. Effusion samples obtained before definitive PM diagnosis were interrogated using BRCA1 ‐ associated protein 1 gene ( BAP1 ), cyclin‐dependent kinase inhibitor 2A gene ( CDKN2A ) and cytologic evaluation to assess whether early or possible in situ disease could be characterized. METHODS: All cases of PM diagnosed between January 2008 and December 2019 were identified at a tertiary referral center. Patients who had a pleural fluid sample collected 24 months before the diagnosis were selected, numbering 8 in total. The cytomorphology of each sample was reviewed; and, retrospectively, BAP1 immunohistochemistry (IHC) and CDKN2A fluorescence in situ hybridization (FISH) were performed on initial and diagnostic samples. RESULTS: The initial samples were deemed benign in 5 cases and atypical mesothelial proliferations in 3 cases. A spectrum of apparently normal to atypical cytomorphologic changes was identified. BAP1 loss was present in 6 of 8 initial cases, whereas CDKN2A homozygous deletion was identified in 1 of 7 initial cases. Either abnormality was identified in 7 of 8 initial samples. CONCLUSIONS: Detectable abnormalities of BAP1 IHC and CDKN2A FISH were present in pleural fluid specimens before the development of cytomorphologic features diagnostic of PM. This is the largest series to date describing cytology samples early in the course of PM development, thereby highlighting a possible cytological equivalent for mesothelioma in situ. Abstract : Abnormalities in cytomorphology, BAP1, and CDKN2A are present in pleural fluid specimens before the development of cytomorphologic features diagnostic of pleural mesothelioma. This case series describes cytology samples taken early in the course of pleural mesothelioma development, thereby highlighting a possible cytologic equivalent for mesothelioma in situ.